SHOCK INDUCES ENDOTHELIAL PERMEABILITY AFTER TRAUMA THROUGH INCREASED ACTIVATION OF RHOA GTPASE. Issue 6 (21st December 2022) - DeBot, Margot; Mitra, Sanchayita; Lutz, Patrick; Schaid, Terry R.; Stafford, Preston; Hadley, Jamie B.; Hom, Patrick; Sauaia, Angela; Silliman, Christopher C.; Moore, Ernest E.; Cohen, Mitchell J.
ABSTRACT: Introduction: Severely injured patients develop a dysregulated inflammatory state characterized by vascular endothelial permeability, which contributes to multiple organ failure. To date, however, the mediators of and mechanisms for this permeability are not well established. Endothelial permeability in other inflammatory states such as sepsis is driven primarily by overactivation of the RhoA GTPase. We hypothesized that tissue injury and shock drive endothelial permeability after trauma by increased RhoA activation leading to break down of endothelial tight and adherens junctions. Methods: Human umbilical vein endothelial cells (HUVECs) were grown to confluence, whereas continuous resistance was measured using electrical cell-substrate impedance sensing (ECIS) Z-Theta technology, 10% ex vivo plasma from severely injured trauma patients was added, and resistance measurements continued for 2 hours. Areas under the curve (AUCs) were calculated from resistance curves. For GTPase activity analysis, HUVECs were grown to confluence and incubated with 10% trauma plasma for 5 minutes before harvesting of cell lysates. Rho and Rac activity were determined using a G-LISA assay. Significance was determined using Mann-Whitney tests or Kruskal-Wallis test, and Spearman ρ was calculated for correlations. Results: Plasma from severely injured patients induces endothelial permeability with plasma from patients with both severe injury and shock contributing most to this increased permeability. Surprisingly, Injury Severity Score (ISS) does not correlate with in vitro trauma-induced permeability (−0.05, P > 0.05), whereas base excess (BE) does correlate with permeability (−0.47, P = 0.0001). The combined impact of shock and injury resulted in a significantly smaller AUC in the injury + shock group (ISS > 15, BE < −9) compared with the injury only (ISS > 15, BE > −9; P = 0.04) or minimally injured (ISS < 15, BE > −9; P = 0.005) groups. In addition, incubation with injury + shock plasma resulted in higher RhoA activation ( P = 0.002) and a trend toward decreased Rac1 activation ( P = 0.07) compared with minimally injured control. Conclusions: Over the past decade, improved early survival in patients with severe trauma and hemorrhagic shock has led to a renewed focus on the endotheliopathy of trauma. This study presents the largest study to date measuring endothelial permeability in vitro using plasma collected from patients after traumatic injury. Here, we demonstrate that plasma from patients who develop shock after severe traumatic injury induces endothelial permeability and increased RhoA activation in vitro . Our ECIS model of trauma-induced permeability using ex vivo plasma has potential as a high throughput screening tool to phenotype endothelial dysfunction, study mediators of trauma-induced permeability, and screen potential interventions.